1984
DOI: 10.1042/bj2180841
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation in vivo of the P light chain of myosin in rabbit fast and slow skeletal muscles

Abstract: 1. The P light chain of myosin is partially phosphorylated in resting slow and fast twitch skeletal muscles of the rabbit in vivo. The extent of P light-chain phosphorylation increases in both muscles on stimulation. 2. Rabbit slow-twitch muscles contain two forms of the P light chain that migrate with the same electrophoretic mobilities as the two forms of P light chain in rabbit ventricular muscle. 3. The rate of phosphorylation of the P light chain in slow-twitch muscle is slower than its rate of phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
1
21
2
Order By: Relevance
“…They were designated as LC-2, LC2*, LC-2P (the phosphorylated form of LC-2), and LC-2*P (the phosphorylated form of LC-2*), following the nomenclature of Price et al 31 We observed two phosphorylatable P-LC in the ventricle but only one phosphorylatable P-LC in the atrium of human and pig even after preincubation of skinned fibers with MLCK. This observation is in agreement with the concept of Westwood et al, 35 who showed that a P-LC polymorphism exists in slow but not in fast muscle of mammalia as the atrium of human and pig showed a higher shortening velocity than the ventricle. In contrast, Price et al 31 observed two phosphorylatable P-LC in the human atrium.…”
Section: Figure 3 Characterization Of the Myosin P Light Chain Of Thsupporting
confidence: 82%
“…They were designated as LC-2, LC2*, LC-2P (the phosphorylated form of LC-2), and LC-2*P (the phosphorylated form of LC-2*), following the nomenclature of Price et al 31 We observed two phosphorylatable P-LC in the ventricle but only one phosphorylatable P-LC in the atrium of human and pig even after preincubation of skinned fibers with MLCK. This observation is in agreement with the concept of Westwood et al, 35 who showed that a P-LC polymorphism exists in slow but not in fast muscle of mammalia as the atrium of human and pig showed a higher shortening velocity than the ventricle. In contrast, Price et al 31 observed two phosphorylatable P-LC in the human atrium.…”
Section: Figure 3 Characterization Of the Myosin P Light Chain Of Thsupporting
confidence: 82%
“…With respect to phosphorylation of P light chain isolated from rabbit soleus muscle, these results are dissimilar to those reported by Westwood et al (1984). They found that fused tetanic contraction of rabbit soleus muscle resulted in a large increase in the phosphate content of two forms of P light chain.…”
Section: Westwood Et Al (1984)contrasting
confidence: 82%
“…As a consequence, the high basal value of 0.5 mol phosphate/mol P light chain reported by Stull and High (1977) was probably an artifact of the precontraction. Westwood et al (1984) also reported a basal P light chain phosphate content of 0.50 mol phosphate/mol P light chain in combined frozen samples of rabbit tibialis anterior and extensor digitorum longus muscles. The reason for this elevated basal value may have been due to slow freezing of large 3-5-g biopsy samples.…”
Section: Discussionmentioning
confidence: 92%
“…a pair of essential light chains (MELC) and a pair of regulatory (phosphorylatable) light chains (MRLC) [l]. Phosphorylation of MRLC by Ca2 +-calmodulin-dependent myosin light chain kinase (MLCK) is considered in smooth muscle and nonmuscle cells to be a trigger event initiating the interaction of myosin with actin [2, 31. Only a single isoform of MRLC was detected in rabbit fast-twitch skeletal muscle in two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) under dephosphorylated condition [4]. In contrast, two isoelectric variants of cardiac (or slow-twitch skeletal) MRLC have been reported in mammals [5] and in the chicken [6].…”
mentioning
confidence: 99%